Legal Culture in the Management of Life Insurance Companies in Indonesia - Kusuma Wardhani, Indah (KnE Social Sciences, 2024)
In the last ten years, people have been made uneasy by various cases of life insurance companies that have failed to pay. Moreover, the involvement of prominent companies in these cases reduced public trust in them. In these cases, the influence of legal culture is apparent in the management of life insurance companies. Therefore, this study aims to investigate the factors that caused the life insurance companies to fail to pay, the legal culture underlying the management of these companies and the efforts that must be made to improve this culture. The research method employs normative legal research, supported by empirical legal research. The factors causing life insurance companies to default consist of fraud in the company’s financial statements, unreasonably high-interest rates on unit-linked insurance products, and a lack of optimal application of risk management in life insurance companies. The legal culture of their management has not developed in a better direction, leading to an inability to fulfill their obligations. Examples of steps to improve the legal culture include conducting education and training for life insurance company managers, making remuneration policies to encourage behavior that follows the prudential principle, and creating guidelines for managers on ethical business values and conduct. Keywords: legal culture, life insurance companies